Rapid and Non-Destructive Analysis of Plant Material Using FTIR and Chemometric Methods - Salsabilla, Bunga Indra; Muchtaridi, Muchtaridi; Megantara, Sandra; Novitasari, Dhania; Musfiroh, Ida (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Plant material analysis requires efficient, reliable, and sustainable methods for characterization, authentication, and quality control. Fourier Transform Infrared Spectroscopy (FTIR), combined with chemometrics, has emerged as a non-destructive approach that requires minimal sample preparation. This review summarizes developments and applications of FTIR chemometrics in plant analysis from 2015 to 2025, based on more than 32 published studies. The evolution of data analysis is described from classical techniques, including Principal Component Analysis and Partial Least Squares, to machine learning methods such as Support Vector Machines and Random Forests. Various FTIR modes, namely ATR FTIR, DRIFTS, and FTIR PAS, are discussed for analyses of leaves, roots, rhizomes, flowers, fruits, and fossilized plant materials. Reported applications include species identification with accuracies approaching 100%, geographic origin authentication with 77-94% accuracy, detection of adulteration in high-value commodities such as saffron, quantification of bioactive constituents with determination coefficients of 0.96-0.99, and assessment of environmental or agronomic influences on plant composition. Although challenges remain, particularly matrix complexity and calibration transfer, FTIR chemometrics represents a sustainable, rapid, and cost-effective tool for research and industrial quality control. Future directions emphasize the global integration of artificial intelligence and instrument miniaturization.